BINGE ALCOHOL ADMINISTRATION ON PREGNANT RATS RESULTS IN DECREASING OF INSULIN LIKE GROWTH FACTOR-1 AND ALDEHYDE DEHYDROGENASE, INCREASING APOPTOSIS INDEX, AND FETAL ALCOHOL SYNDROME IN OFFSPRINGS. - Suherman, Sutjahjo; Soetjiningsih, S.; Suastika, Ketut; Astawa, I Nyoman Mantik (BALI MEDICAL JOURNAL; Vol 5 No 1 (2016), 2016)
Background: Addiction of alcoholic beverage by early pregnancy women results in fetal alcohol syndrome of her baby. This study aims to investigate fetal alcoholic syndrome due to binge alcoholic drinking by the early pregnant of wistar rat. Methods: This is an experimental study applying posttest only control group design. Wistar Rats were in preconditioning for pregnancy and divided into two groups, i.e. one group was fed with normal feeding and the other group was fed with normal feeding and 40% of ethanol. The off spring then were observed and divided into three groups, i.e. normal fetal, normal fetal from the mother fed with ethanol, and fetal alcoholic syndrome. Insulin like growth factor (IGF-1), aldehyde dehydrogenase (ALDH), apoptosis index, pathology of their brain and heart were observed. The different of all these parameters were then compared by applying one way anova, and considered significant at p < 0.05. Results: In this study we found that there were fetals alcoholic syndrome (FAS) due to the mother of the Wistar Rat fed with ethanol during their pregnancy. There were also a significant different of IGF-1, ALDH, apoptosis index between these three groups (p < 0.05), i.e. normal baby, normal fed with ethanol, and FAS. IGF-1 for these three groups were 56.59±0.52 ng/ml, 55.17±2.41 ng/ml, and 36.64±4.86 ng/ml, respectively. ALDH for the groups were 21.41±2.38 ng/ml, 21.16±4.77 ng/ml, and 17.05±2.68 ng/ml, respectively. Their brain apoptosis indexes were 4.56±0.78, 4.58±1.17, and 7.86±1.31, respectively. Heart apoptosis indexes were found 2.81±1.18, 5.36±1.37, and 7.50±1.43, respectively. Conclusion: Binge alcohol drinking during pregnancy of Wistar Rat results in FAS and identified by decrease of IGF-1, ALDH and increase of brain apoptosis index and heart apoptosis index of the off spring.
Keywords: addiction; alcoholic; drinking; apoptosis, index.